2018
DOI: 10.1007/s10549-018-4834-7
|View full text |Cite
|
Sign up to set email alerts
|

The combined presence of CD20 + B cells and PD-L1 + tumor-infiltrating lymphocytes in inflammatory breast cancer is prognostic of improved patient outcome

Abstract: Purpose: To evaluate protein expression of PD-L1 and CD20 as prognostic biomarkers of patient outcome in inflammatory breast cancer (IBC) samples. Methods: PD-L1 and CD20 protein expression was measured by immunohistochemistry in 221 pretreatment IBC biopsies. PD-L1 was assessed in tumor cells (PD-L1+ tumor cells) and tumor stromal infiltrating lymphocytes (PD-L1+ TILs); CD20 was scored in tumor-infiltrating B cells. Kaplan–Meier curves and Cox proportional hazard models were used for survival analysis. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 33 publications
11
56
2
Order By: Relevance
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In addition, it has been reported that PD‐L1 is differentially expressed across different BC subtypes. In particular, available evidence consistently reports greater expression of PD‐L1 in the TN subtype (up to 60% of PD‐L1 expression) compared with non‐TNBC . These data appear to be coherent with the observation that PD‐L1 tumor expression is positively associated with stromal tumor‐infiltrating lymphocytes (TILs) in this BC subtype , which is known to be more frequently infiltrated by stromal TILs than non‐TNBC , as summarized in Table , thus possibly suggesting that these two immune biomarkers tend to run parallel.…”
Section: Methodssupporting
confidence: 74%
“…Data on PD‐L1 expression in HER2‐positive BC are more controversial. In fact, whereas in some studies HER2 positivity has been correlated with higher expression of PD‐L1 (up to 50%) compared with HER2‐negative BC , others failed to report any difference .…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…[21]. It has also been demonstrated that significant anti-CSC immunity was induced by dendritic cell vaccine basing on CSC both in vitro and in immune-competent hosts [8,22]. B lymphocytes were recently found to play a pivotal role in the cancer immune by being an assistant for T lymphocyte [23].…”
Section: Discussionmentioning
confidence: 99%
“…Coexistence of CD20+ TILs and PD-L1+ tumour cells were significantly associated with better DOI: 10.1159/000504055 survival,a high pCR rate, and high infiltration of TILs in triple-negative IBC. High CD20+ and PD-L1+ TIL infiltration correlated with fewer relapses, a high pCR, and higher rates of DFS and BCSS [42]. PD-L1 expression in tumour cells was positively associated with a high infiltration of intratumoural/peritumoural CD8+ TILs and CD163+ macrophages in HER2-positive breast cancer [43].…”
Section: Cd20+til and Pdl-1 Expression In Breast Cancermentioning
confidence: 93%